Tandem generation of isocoumarins in hollow microporous organic networks: nitrophenol sensing based on visible light. Issue 21 (11th May 2016) - Park, Nojin; Ko, Kyoung Chul; Shin, Hee-Won; Lee, Sang Moon; Kim, Hae Jin; Lee, Jin Yong; Son, Seung Uk
Abstract : Hollow microporous organic networks bearing isocoumarin moieties (H-IC-MONs) were prepared via a tandem synthetic approach and applied to nitrophenol sensing using visible light. Abstract : Hollow microporous organic networks bearing isocoumarin moieties (H-IC-MONs) were prepared via a tandem synthetic approach. Pd catalysts conducted the networking of building blocks by the Sonogashira coupling with the concomitant generation of isocoumarins through cyclization. The H-IC-MONs showed visible light absorption and emission properties and were applied to nitrophenol sensing using visible light.